Strategies to promote reading (Journal of Parents and Teachers, 2013)
The author offers some suggestions for getting the children to enjoy reading by recognizing the great value of this activity. She opts specially for the stories but pointing out when and how should be told and stresses the role of parents and teachers as key for the motivation of the children.
Keywords: Tale; Reading taste; Motivation; Learning conditions; family and school; Education